Wachstumsschwäche, Bankenmalaise und Bankenregulierung - Martin Hellwig (Wirtschaftsdienst, 2017)
– The paper contributes to the ongoing discussion about appropriate policies towards banks when economic growth is lagging. Whereas the European Commission and representatives of the German government argue that strict banking regulation harms economic growth, the comparison between Europe and the US suggests that the opposite is true and that weak economic growth, even in Germany, is due to the insuffi ciency of the clean-up following the financial crisis. The ECB's attempts to force banks to increase their lending exacerbate their weaknesses. The paper warns against confusing mere growth in demand, fuelled by credit and possibly unsustainable, with sustainable output growth, fuelled by appropriate lending and investments. Such investments will not be forthcoming if banks are weak and their decisions are distorted by debt overhang and hidden insolvency. Hopes that debt overhang will be reduced over time are illusory if banking is unprofitable. Immediate recapitalisations would be better and should be possible if banks are perceived as solvent. The view that strict banking regulation harms economic growth is in conflict with experience, including the tightening of capital requirements since 2010.
Keywords: E58; G21; G28; 330